Outcomes of haemoglobin Bart's hydrops fetalis following intrauterine transfusion in Ontario, Canada. Issue 1 (2nd July 2020) - Zhang, Hui Jue; Amid, Ali; Janzen, Laura A; Segbefia, Catherine I; Chen, Shiyi; Athale, Uma; Charpentier, Karen; Merelles-Pulcini, Manuela; Seaward, Gareth; Kelly, Edmond N; Odame, Isaac; Waye, John S; et al.
Abstract : Objectives: With improved access to intrauterine transfusion (IUT), more fetuses with haemoglobin Bart's hydrops fetalis (HBHF; homozygous α 0 -thalassaemia) will survive. Design: To evaluate the long-term outcome of affected fetuses with and without IUT in Ontario, Canada, we retrospectively collected data on IUTs and pregnancy outcomes in all cases of HBHF, from 1989 to 2014. Clinical outcome and neurocognitive profiles of long-term survivors were also collected and compared with data from 24 patients with transfusion-dependent β-thalassaemia (TDT-β). Results: Of the 99 affected pregnancies (93 prenatally diagnosed), 68 resulted in miscarriage or elective termination of pregnancy. Twelve mothers (12%) continued their pregnancies without IUT, and none of those newborns survived the first week of life. All 13 fetuses that received IUT(s) were live-born, but 3 died due to severe hydrops at birth and 1 died due to infection. The remaining nine survivors, in comparison with TDT-β patients, had earlier iron overload requiring iron chelation therapy. Endocrinopathies and short stature were more frequent in these patients. Neurocognitive outcome was not significantly affected in five patients who were assessed, and none were diagnosed with intellectual impairment. In three patients, MRI studies demonstrated brain white matter changes in keeping with 'silent' ischaemic infarcts. Conclusions: In patients with HBHF, IUT is associated with improved survival. While acceptable neurocognitive outcome can be expected, these patients have more clinical complications compared with their TDT-β counterparts. The clinical and neurocognitive outcomes of HBHF should be discussed in detail when counselling and offering IUT for patients.